Pengaruh Pemberian Beberapa Jenis Pupuk Organik Padat Terhadap Pertumbuhan dan Hasil Cabai Merah, Bawang Merah, dan Bawang Daun - Bagus Nur Rochman (Gontor AGROTECH Science Journal, 2015)
The importance of organic fertilizers in a cropcultivation is to restore land productivity and reduce the useof synthetic fertilizers. Various ways has been developed tocreate quality organic fertilizer, for plants vegetables suchas red chili, shallots and leek with low input. The aims ofthis study were to determine the effect of some kind of solidorganic fertilizer on the growth and yield of red chili, shallots and leek, and to know the best organic fertilizer for each typeplants. The experimental design used is Split Plot Designwith the basic design of Randomized Complete DesignBlockwith 3 replications as blocks. The main plots consistedof 3 species of plant vegetables. The subplot consisted of 5kinds of solid organic fertilizer and without any treatmentsas control. There were 18 plots per block or the totals were54 plots. The results showed that aplication of several typesof solid organic fertilizer signifi cantly increased the growthand yield of red chilli, shallot and leek. Solid organic fertilizerfrom community A showed that the highest signifi cantlyincreased the growth and yield of red chilli. Combinationof organic fertilizer and Rock Phosphate (RP) 2.4 ton / hashowed the highest growth and yield of leek. Combinationof organic fertilizer and K-feldspar 0.6 ton / ha showed thehighest growth and yield of shallot